The Existence of Religious Moderation in the Freedom Era Learn on the Independent Campus at a Religious Higher Education in Bali - I Gede Suwindia; Ni Nyoman Kurnia Wati (International Journal of Interreligious and Intercultural Studies, 2023)
This study aims to examine religious moderation in religious tertiary institutions, especially Hinduism in the independent era of independent campus learning. This research uses quantitative and qualitative methods (mixed methods). The research subjects on the existence of religious moderation in the MBKM era were 1 person from a higher education institution, 3 MBKM implementers in this case were lecturers, and 50 moderators in MBKM, namely students. The data collection method in this research uses interviews and questionnaires. The data analysis method is qualitative. The concept of religious moderation was translated at each tertiary institution in the era of the independent campus through subjects such as religious moderation, multicultural studies, anti-corruption courses, and several other courses which included religious moderation. Obstacles faced in implementing religious moderation in the era of independent learning on an independent campus at religious tertiary institutions in Bali include limited facilities and infrastructure, unable to prepare special facilities/places of worship for students of different religions. Adjusting to the new curriculum and making moderation a subject requires a good thought for both the policy makers and the lecturers. The strategy undertaken in dealing with obstacles in the implementation of religious moderation in the era of independence was to study independent campuses at religious universities in Bali by strengthening religious moderation. Collaborating with religious universities other than Hinduism, creating guest lecturer programs to fill in courses that are integrated with religious moderation content, conducting religious moderation workshops that are trained by practitioners or by experts from various religions.